1977
DOI: 10.1104/pp.60.4.538
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antimycin A and Uncouplers on Anaerobic Photosynthesis in Isolated Chloroplasts

Abstract: Anaerobiosis depresses the light-and bicarbonate-saturated rates of 02 evolution in intact spinach (Spinacia oleracea) chloroplasts by as much as 3-fold from those observed under aerobic conditions. These lower rates are accelerated 2-fold or more by the addition of 1 ,UM antimycin A or by low concentrations of the uncouplers 0.3 mM NH4CI or 0.25 jaM carbonyl cyanide m-chlorophenylhydrazone. Oxaloacetate and glycerate 3-phosphate reduction rates are also increased by antimycin A or an uncoupler under anaerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 26 publications
(48 reference statements)
1
21
0
Order By: Relevance
“…Possible scenarios involve metabolic shuttles between the chloroplast and the mitochondrion. Oxaloacetate and 3-phosphoglycerate reduction rates have been shown to increase in the absence of CEF in isolated chloroplasts under acceptor-limiting conditions (Slovacek and Hind, 1977). Similar in vitro enzymatic assays showed that the malate valve could operate as rapidly as the major (linear) photosynthetic flow rate (Fridlyand et al, 1998).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Possible scenarios involve metabolic shuttles between the chloroplast and the mitochondrion. Oxaloacetate and 3-phosphoglycerate reduction rates have been shown to increase in the absence of CEF in isolated chloroplasts under acceptor-limiting conditions (Slovacek and Hind, 1977). Similar in vitro enzymatic assays showed that the malate valve could operate as rapidly as the major (linear) photosynthetic flow rate (Fridlyand et al, 1998).…”
Section: Discussionmentioning
confidence: 67%
“…It parallels some earlier observations. In isolated chloroplasts, a slowing down of linear electron flow under acceptor-limited conditions was attributed to proton gradient backpressure generated by CEF (Slovacek and Hind, 1977). In tobacco (Nicotiana spp.)…”
Section: Discussionmentioning
confidence: 99%
“…The effect of antimycin A on photosynthetic activities in thylakoids and intact chloroplasts is complex and apparently depends on the experimental conditions involved (7,14,19,20,22,23,25,28). Figure 1 shows that the photoreduction of methyl viologen in intact chloroplasts is insensitive to antimycin A up to 4 Am in the presence and absence of 10 mm NH4CL.…”
Section: Resultsmentioning
confidence: 99%
“…For example, red light was used in the experiments of Heber et al (14) while the uptake of phosphate had been used as an indicator reaction in the evidence discussed by Simonis and Urbach (24) and Gimmler (1 1). The reported stimulation of photosynthesis in chloroplasts by antimycin A under anaerobic and aerobic conditions (19,22,25,28) indicates the complex nature of the direct and indirect effect of antimycin A on photosynthetic carbon metabolism. However, like Heber et al (14), we have never observed stimulation of photosynthesis by antimycin A in intact chloroplasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation